Determining organizational stress level of resident physicians in an university hospital [Bir üniversite hastânesinde çalişan asistan doktorlarin örgütsel stres düzeylerinin deǧerlendirilmesi] - (:unkn) unknown (My University, 2008)
Purpose: In this article, resident physicians' who worked in a university hospital determined organizational stress sources, organizational annoyances, and organizational stress levels. Method: Research type was cross-sectional study. 200 residents were working in university hospital and 166 residents have involved the study (83.0%). Data obtained with questionnaire in under observation. Questionnaire designed with two sections; first part was including personal information, second part was including stress an assessment question which is developed by Inci Artan named "Organizational Stress Resources Scale". Findings: Participants genders were 51.8% female, 48.2% male, 30.7% were married. Residents who participated to study were working 44.6% in Internal medicine branches, 31.3% in surgical branches, 24.1% in basic sciences branches. Residents declared first organizational stress resource as salary dissatisfaction. Other reasons were infrastructure, tools and device insufficiency of hospital, insufficient professional development facilities and reward mechanism, and few career possibilities. According to age groups organizational stress point and organizational annoyance point was highest between young residents [22-25 aged group] [respectively, p=0.048 p=0.024]. When professional development dimension was assessed, female residents took statistically significant, and higher organizational stress points than men residents. Discussion and Conclusion: Stress in work environment develops personal and organizational outcomes. In this condition, workers productivity could diminish, absenteeism and quitting from job could increase. In our study has shown that residents work under organizational stress in university hospital. Stress reducing strategies will improve workers productivity. All organizational components need wide intervention for development less stressful organization in university hospital work environment.
Keywords: Organizational stress; Physician; University hospital; Work stress